Neuroanatomical signatures of genetic risk for Alzheimer's disease in healthy adults. (1st February 2022) - Waters, Sheena; Watson, Cameron; Jacobs, Benjamin M.; Foote, Isabelle F.; Dey, Sumit; Noyce, Alastair J.; Marshall, Charles R.
Abstract: Background: Early detection of Alzheimer's disease (AD) is critical for the development of interventions that delay or prevent neurodegeneration. Previous studies suggest that genetic liability to AD may be associated with structural brain changes that start 20‐30 years before symptoms manifest. Method: We derived an optimised AD polygenic risk score (AD‐PRS) using imputed genotype data from 488, 377 participants in UK Biobank. We examined the structural brain correlates of AD‐PRS in 27, 496 healthy UK Biobank participants using voxel‐based morphometry (VBM) with multiple regression and additionally performed regression analyses using image‐derived phenotypes (IDPs) from T1‐weighted and diffusion‐weighted magnetic resonance images. Result: VBM revealed that high AD‐PRS was associated with reduced grey matter volume (GMV) in bilateral hippocampus and putamen (family wise error correction, p<0.05). IDP analysis further revealed GMV deficits in a bihemispheric limbic network incorporating hippocampus, parahippocampal gyrus, ventral striatum, orbitofrontal cortex, and thalamus, as well as reduced white matter integrity in the major white matter tracts of this network (fornix, cingulum hippocampus, and thalamic radiation). Conclusion: Genetic liability to AD is associated with preclinical neurodegeneration in grey and white matter components of the limbic system. Integrity of this network could serve as a marker of preclinical AD and an outcome measure in prevention trials.